The value of a liaison neurology service in a district general hospital. Issue 1025 (23rd December 2010) - McColgan, P; Carr, A S; McCarron, M O
Abstract : Background: Healthcare development in the UK has resulted in an increase in neurologists working in district general hospitals. Methods: The aim of the study was to determine the use of a neurologist for inpatient diagnosis and management, and to measure a neurologist's diagnostic reliability in a district general hospital over a 27-month period. Patient data were prospectively recorded. Follow-up was performed independently by two clinicians reviewing the medical notes. Reasons for diagnostic change were determined. Results: 306 inpatients were referred to the neurologist between 1 January 2007 and 31 March 2009 (2% of medical admissions). Mean (SD) age was 49.3 (18.8) years, and the female/male ratio was 1.2:1. Epilepsy and stroke were the most common diagnoses. Diagnostic concordance between referring physician and neurologist ranged from κ score 0.13 (spinal pathology) to 0.83 (central nervous system infection). Neurological opinion resulted in diagnostic change in 38.2% and management change in 88.8%. Only 1.6% of patients remained without a diagnosis, a fourfold improvement from physician referral. After medical records had been reviewed, 3.3% of inpatient diagnoses (10 of 306 patients) changed from the original diagnosis by the neurologist. Specialist investigation helped in revising diagnoses in four of the 10 diagnostic changes. Conclusion: This study shows that in a district general hospital a neurologist can contribute to inpatient diagnosis and management with minimal diagnostic change over time, suggesting reliability of this service.